Factors Affecting Skill of Teachers in the Agricultural University - K. T. Lahariya,; N. R. Koshti, (Journal of Agricultural Extension Management, 2025)
Skill in teaching is the manifestation of the knowledge of a subject and the communication ability of a teacher. The skills possessed by a teacher are of utmost importance in transmitting knowledge to the students. Keeping this in view, the objectives of this study are to assess the skill possessed by teachers to impart instruction in the Agricultural University; and find out the relationship between selected socio-personal and psychological characteristics and skill of teachers